A Study on Small Vehicle Structure in Rear Under-Ride Impact by Using A CAE Based Methodology - Nguyen Phu Thuong Luu; Ly Hung Anh (Journal of Engineering and Technological Sciences, 2022)
This study simulated and evaluated the safety of a small car structure in a collision with the rear of a truck. The parameters of bumpers currently used in Vietnam were employed to build a model of the rear truck bumper. The setting of simulation conditions was based on the NCAP (New Car Assessment Program) crash test. According to actual crash conditions, a collision simulation was performed with different vehicle speeds from 40 to 60 km/h, corresponding to the case of a passenger vehicle moving in a city colliding with a truck standing still. In addition, the percentage of rear-end collision was also taken into account, just like in real-world collisions, at 25%, 50%, and full rear impact. The simulation results were analyzed and evaluated according to the IIHS rating (Institute Insurance for Highway Safety). The results from different case studies showed that the rear bumper typically used on trucks is only safe for passenger cars in a collision at a low speed of 40 km/h and that in a collision at a higher speed will affect the passenger’s safe space and cause high injuries and casualties. Therefore, it is necessary to improve safety by optimizing the rear bumper design and the frontal structure of the small car chassis.